Fatal pulmonary infection by trimethoprim-sulfamethoxazole resistant Nocardia otitidiscaviarum: report of two cases and review - Rushika Saksena; Dabet Rynga; Santosh Rajan; Rajni Gaind; Reetika Dawar; Raman Sardana; Manas Kamal Sen; Jagdish Chandra Suri (Journal of Infection in Developing Countries)
Introduction: Nocardia otitidiscaviarum is a rare cause of human infections, mostly causing cutaneous and lymphocutaneous infections of mild severity. We report two cases of fatal pulmonary infection caused by Nocardia otitidiscaviarum in elderly patients.